Development and characterisation of equine in vitro models of respiratory inflammation and resolution - Beynon, Charlotte Louise (2013)
BACKGROUND Chronic respiratory inflammation is a major cause of recurrent airway obstruction (RAO) in mature horses. RAO has aetiological and clinical similarities to human asthma. Remodelling of airway tissue after bronchial inflammation is evident in RAO and human asthma. Severe asthma in humans is associated with defective lipoxin A4 (LXA4) synthesis and abnormal expression of specific lipoxin receptor (ALX). Arachidonic acid metabolite LXA4 modulates acute inflammation in a number of species and models of acute inflammation. Dysfunctional LXA4 synthesis and/or expression of the ALX receptor may contribute to the chronic inflammatory response seen in asthma. Abnormal LXA4 and/or ALX expression may also be present in horses with RAO thereby promoting airway remodelling. HYPOTHESIS Equine inflammation and its resolution can be modelled in vitro using respiratory epithelial and smooth muscle models. AIMS To develop an in vitro equine respiratory model of respiratory epithelium and airway smooth muscle. Characterise the response of this model to exogenous lipolysaccharide (LPS) and lipoxin A4 on selected molecules associated with inflammation and inflammatory resolution. METHODS Primary equine tracheal epithelial (ETE) cells were obtained from trypsindissociation of tracheal epithelial tissue derived from healthy horses with no sign of inflammation at post-mortem. Primary airway smooth muscle (ASM) cells were cultured from explants of equine trachealis muscle. Near confluent (70-75%) ETE and ASM cells were stimulated with 0.1, 10 and 100µg/ml LPS at 4 and 24 hrs (ETE cells) or 12, 24 and 72hrs (ASM cells). Expression of COX-2 mANA in these cells was used to determine a suitable time point and LPS concentration to induce inflammation. Inflammatory resolution was then examined by comparing the selected time points and LPS concentrations with the response of ETE and ASM cells to 15 minutes incubation with 100µM LXA4 and LXA4/LPS treatment. Finally, the inflammatory relationship between the epithelium and smooth muscle layer was examined by a co-culture model of ETE and ASM cells. Conditioned media from ETE cells treated with 0.1µg/ml LPS, 100µM LXA4 and LXA4/LPS treatment for 24hrs was used to culture ASM cells for a further 24hrs. To examine inflammation and its resolution, selected genes, namely ALX, toll-like receptor 4 (TLA-4), tumour-necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β), inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) were amplified and quantified by real time PCR. ALX and COX-2 proteins were monitored by Western blot and nitric oxide (NO) levels measured by fluorometric analysis. Values for statistical analysis of ETE and ASM cells were obtained with a two and one-way ANOVA and Tukey's multiple comparisons test. RESULTS Primary ETE and ASM cells were identified by positive immunocytochemical staining with pan cytokeratin-26 and alpha-smooth muscle actin respectively. Treatment of ETE cells with 0.1µg/ml LPS for 24hrs increased iNOS and COX-2 mRNA levels, and significantly increased mRNA expression for ALX, TLR-4 TNF-α and IL-1 j β mRNA (p values <0.05). ASM cells incubated over 72hrs incubation with 0.1119/ml LPS showed increased expression of selected genes but only significant increases in COX-2 mRNA were observed (p values <0.05). Incubation of ETE and ASM cells with LXA4 did not significantly increase or inhibit inflammation as measured by real time PCR, Western blot and fluorometric anlaysis. Western blotting showed some inhibition of COX-2 protein in ASM cells but not ETE cells at 72hrs after LXA4 treatment. Fluorometric analysis of NO levels in ETE and ASM cells showed no significant difference after treatment in either cell type. No noticeable evidence of inflammation or inhibition of inflammation was observed in the co-culture model of ETE and ASM cells. CONCLUSION It was concluded that an in vitro equine model of respiratory epithelium and smooth muscle was successfully established. It was possible to induce partial inflammation in ETE and ASM cells but inflammatory resolution could not be definitively shown in either cell type.